2023
DOI: 10.1002/hbm.26430
|View full text |Cite
|
Sign up to set email alerts
|

Planning ahead: Predictable switching recruits task‐active and resting‐state networks

Abstract: Switching is a difficult cognitive process characterised by costs in task performance; specifically, slowed responses and reduced accuracy. It is associated with the recruitment of a large coalition of task‐positive regions including those referred to as the multiple demand cortex (MDC). The neural correlates of switching not only include the MDC, but occasionally the default mode network (DMN), a characteristically task‐negative network. To unpick the role of the DMN during switching we collected fMRI data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…In the Core DMN ROI, we first examined the basic switch effect, contrasting against taskrepeat trials, and averaging across all other factors (Figure 3A). Replicating previous findings of the DMN switch effect (Crittenden et al, 2015;Kurtin et al, 2023;Smith et al, 2018;Zhou et al, 2024), a t-test confirmed a significant increase in Core DMN activity at task switches (averaged across switch types) compared to task repeats (t35 =4.46, p<0.01, BF10=301). A t-test also found greater Core DMN activity for within-group-between-domain switches compared to within-group-within-domain switch trials (t35=4.43, p<0.01, BF10=280).…”
Section: Simple Switch Effect Replicated In Core Dmnsupporting
confidence: 81%
See 1 more Smart Citation
“…In the Core DMN ROI, we first examined the basic switch effect, contrasting against taskrepeat trials, and averaging across all other factors (Figure 3A). Replicating previous findings of the DMN switch effect (Crittenden et al, 2015;Kurtin et al, 2023;Smith et al, 2018;Zhou et al, 2024), a t-test confirmed a significant increase in Core DMN activity at task switches (averaged across switch types) compared to task repeats (t35 =4.46, p<0.01, BF10=301). A t-test also found greater Core DMN activity for within-group-between-domain switches compared to within-group-within-domain switch trials (t35=4.43, p<0.01, BF10=280).…”
Section: Simple Switch Effect Replicated In Core Dmnsupporting
confidence: 81%
“…Complicating this broadly consistent picture, recent findings of increased DMN activity, especially of its Core subnetwork, during difficult and externally driven task switches challenge simple views of DMN as a purely 'task-negative', or internally focused network (Crittenden et al, 2015;Kurtin et al, 2023;Smith et al, 2018;Zhou et al, 2024). However, studies requiring people to alternate between two, often similar, tasks, typically activate multiple-demand-like regions, rather than the DMN (Braver et al, 2003;Kim et al, 2012;Monsell, 2003).…”
Section: Introductionmentioning
confidence: 90%
“…Switching from one task to another is cognitively demanding, as demonstrated by performance costs (Monsell, 2003), and is typically associated with activation of brain networks involved in executive control (Braver et al, 2003). Therefore, it is surprising that the Core subnetwork of the default mode network (DMN), which is typically deactivated during difficult external tasks, can also be activated by difficult task switches under some circumstances (Crittenden et al, 2015; Kurtin et al, 2023; Smith et al, 2018). Here we confirmed that, when people must switch between many tasks, or from a brief rest back to a task, DMN regions are activated by task switches relative to task repeats.…”
Section: Discussionmentioning
confidence: 99%
“…DMN activity at task switches is consistent with more general DMN activation at event boundaries in narrative comprehension (Speer et al, 2007) and hierarchical task sequences (Wen, Duncan, et al, 2020), yet is difficult to reconcile with many prominent views of DMN function that emphasise involvement in internally-oriented cognition (Buckner et al, 2008), such as self-related thought (Andrews-Hanna et al, 2010; Davey et al, 2016; Gusnard et al, 2001), autobiographical memory retrieval and mental imagery (Addis et al, 2007; Buckner & Carroll, 2007; Hassabis & Maguire, 2009; Schacter et al, 2007), as well as social cognition (Mars et al, 2012). The difficult, externally-driven switches between fast-paced decisions on simple stimuli, that can activate the DMN (Crittenden et al, 2015; Kurtin et al, 2023; Smith et al, 2018), seemingly afford little opportunity, let alone requirement, for such modes of thought.…”
Section: Introductionmentioning
confidence: 99%
“…When it is the target, search is terminated, but when it is not, attention is guided to a new potential target and the cycle continues. Thus, targets must be maintained in memory over time, but control mechanisms flexibly adjust goals based on sensory outcomes (Badre & Wagner, 2007; Egner, 2023; Kurtin et al, 2023; Poskanzer & Aly, 2023; Rossi et al, 2009; Tunnermann et al, 2021).…”
Section: Introductionmentioning
confidence: 99%